2013
DOI: 10.1007/s12028-013-9881-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ATP-Binding Cassette Polymorphisms on Neurological Outcome After Traumatic Brain Injury

Abstract: Background As important mediators of solute transport at the blood–brain and blood–cerebrospinal fluid barriers, ATP-binding cassette (ABC) transporters (including ABCB1, ABCC1, and ABCC2), impact the bioavailability of drugs and endogenous substrates in the brain. While several ABCB1, ABCC1, and ABCC2 single nucleotide polymorphisms (SNPs) have been identified, their impact on outcome after traumatic brain injury (TBI) is unknown. Hypothesis ABCB1, ABCC1, and ABCC2 SNPs are associated with Glasgow Outcome S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 39 publications
0
28
0
1
Order By: Relevance
“…30,31 In addition, a single nucleotide polymorphism (SNP) for ABCC1 has been shown to be associated with neurological outcome after TBI, 32 although whether this represents a gain or loss of function (or neither) SNP is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 In addition, a single nucleotide polymorphism (SNP) for ABCC1 has been shown to be associated with neurological outcome after TBI, 32 although whether this represents a gain or loss of function (or neither) SNP is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Cousar et al (2013) reported that the C allele of ABCB1 C3435T was associated with a better outcome of TBI patients compared with those carrying the T allele. However, Seven et al (2014) reported that the MDR1 C3435T and G2677T/A polymorphisms were not associated with antiepileptic drug resistance in Turkish epileptic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the association between ABCB1 polymorphisms and neurological disease (Liang et al, 2013;Cousar et al, 2013;Emich-Widera et al, 2013;Seven et al, 2014). Cousar et al (2013) reported that the C allele of ABCB1 C3435T was associated with a better outcome of TBI patients compared with those carrying the T allele.…”
Section: Discussionmentioning
confidence: 99%
“…For example, polymorphisms of the antiexcitotoxic adenosine A1 receptor are strongly associated with the development of posttraumatic seizures in adults with TBI and may help guide anticonvulsant therapy (19). Similarly, adenosine triphosphate (ATP)-binding cassette polymorphisms are associated with outcome after TBI in children (20). ATP-binding cassette proteins are drug transporters at the blood-brain barrier and impact dosing and efficacy.…”
Section: Challenges In Clinical Trial Design Targeting the Managementmentioning
confidence: 99%